Romantic pre-wedding tourism: a lucrative market for a destination’s tourism development? The example of the Dalat climatic resort in Vietnam - Anh Thư Lê (Via@)
In Vietnamese culture, a wedding usually takes place in two or three stages: a first ceremony held in the bride’s home town, a second in the groom’s, and a third at the couple’s residence if they live elsewhere. Although weddings take place in several stages, each one typically involves a single ceremony followed by a reception. After the party, following Western influences and the Doi Moi1 (Turley and Selden, 2019), the bride and groom can set off on their honeymoon. In addition, over the past decade, these ceremonies have often been preceded by a pre-wedding trip and perpetuated by the creation of a photo album. As this item has become one of the essential memorial elements of the entire wedding, it is no longer simply a private keepsake and must be original in order to impress guests and the couple’s social network. Such is its importance that fiancés turned newlyweds use it as a tool to assert their new identity by publishing it on social networks even before the day of the official ceremonies. To meet this demand, pre- and post-wedding destinations (the product’s start and end points, respectively), are becoming increasingly ‘romantic’ to attract this clientele. One of the destinations involved in this new trend is Dalat. As a climatic health resort built by the French during the time of Indochina (1887-1954), the city has been particularly significant in the development of this form of tourism, as “its original image is linked to romanticism” (Jennings and Larcher-Goscha, 2013; Jennings, 2011). In the context of the topic Honeymoon destinations, our article will focus on the theme of pre-wedding tourism products in the setting of Dalat, and will answer the following questions: what role does romantic pre-wedding tourism play in the tourism development of a destination? Why must destinations like Dalat be “sophisticated” to appeal to customers, i.e., offer a wide range of entertainment options and an array of colourful, lively and contemporary products. Is this “romantic” development characteristic of a “kitschification” of the tourism experience (Moles and Wahl, 1969)?